Pengaruh Quality of Work Life terhadap Keterlibatan Kerja dengan Job Satisfaction sebagai Variabel Mediasi - Meutia, Hijir Yoesryna; Hardjo, Suryani; Patisina, Patisina (Universitas Muhammadiyah Metro, 2025)
Female workers at BNN Aceh face significant challenges in balancing work with household responsibilities, as well as dealing with high work pressure and male dominance in leadership positions. This research aims to analyze the influence of quality of work life on work engagement among women at BNN Aceh, with job satisfaction as a mediating variable. The research uses a quantitative method with a positivist approach, collecting data through research instruments and analyzing it statistically to test the hypothesis. Data analysis is performed using Structural Equation Modeling (SEM) with SmartPLS 3.0 to examine the influence of independent, mediating, and dependent variables. The results show that quality of work life (QWL) does not directly affect work engagement. However, QWL significantly influences job satisfaction. Additionally, job satisfaction affects work engagement and acts as a mediating variable in the relationship between QWL and work engagement. These findings suggest that improving job satisfaction can be an effective way to enhance work engagement among female career workers at BNN Aceh.